Formation and inhibition of advanced glycation endproducts in meat and model systems - Chen, Gengjun (Kansas State University, 2016)
Advanced glycation endproducts (AGEs) are formed in many cooked meat products via Maillard browning reactions. Current research suggests consumption of these compounds may be a contributor to chronic diseases such as diabetes and heart diseases. Thus, information on the prevalence and inhibition of these compounds in food is desirable. The first objective was to determine the AGE content, as determined as N[superscript]ε-carboxymethyllysine (CML) level, in cooked meat and fish prepared by general cooking methods recommended by U.S. Department of Agriculture, Food Safety and Inspection Service (USDA-FSIS). We found AGE was detected in all the cooked samples, but the levels depended on the different cooking conditions. Broiling and frying at higher cooking temperatures produced higher levels of CML and broiled beef contained the highest CML content (21.84 μg/g). However, the baked salmon (8.59 μg/g) and baked tilapia (9.72 μg/g) contained less CML as compared to the other samples. In order to investigate the inhibitory effect of selected natural antioxidant on AGEs formation in cooked meat, four cereal brans, wheat (Jagger, JA), triticale (Spring Triticale, ST; Thundercale, TH), and Rye (RY) bran were added to beef patties before cooking. RY (42.0% inhibition), ST (27.5% inhibition), and TH (21.4% inhibition) brans significantly decreased CML formation compared with the control. The inhibition of CML was correlated to the water-holding activity (WHC) of the samples, and the radical scavenging activity of the brans. The effect of cereal bran extracts (JA, ST, TH, and RY), was studied in a bovine serum albumin and glucose (BSA-GLU) model system. The ST extract significantly (P <0.05) inhibited CML formation compared to the control group. ST particularly contained vanillic acid (VA), chlorogenic acid (CHA), gentisic acid (GEA), and ferulic acid (FA), where GEA and CHA mitigated CML with an average percentage decrease of 29.6% for CHA and 51.1% for GEA. It therefore may be useful in preventing AGEs formation by using ST bran as a food addictive, which contains abundant phenolic acids. In summary, current dietary AGEs database will provide important information for use in estimating AGEs exposure, and also these data demonstrate that a significantly reduced intake of dietary AGEs can be achieved by low heat AGE cooking methods such as baking, which can be used at home or in the meat industry. Cereal bran addition to meat products may reduce formation of AGEs that is a desired attribute for the processed meat products industry.
Keywords: Carboxymethyllysine; Cereal branAdvanced glycation endproducts